Evaluation of The Implementation of the Revenue Accounting System for Permits for Sales of Alcoholic Beverages at the Manado City Investment and One Stop Integrated Service Office - Morenna Engelina Evanthe Tuju (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
The Manado City Investment and One Stop Integrated Service Office (DPMPTSP) is a Regional Work Unit (SKPD) whose main source of income is obtained from certain licensing fees. One of them is the Retribution for the Permit for Selling Alcoholic Drinks (ITPMB). The ITPMB levy is a payment for the service of granting a license to sell alcoholic beverages in a certain place. In the process of income SKPD requires an adequate accounting system to assist in decision making. The study aims to determine how the ITPMB income retribution accounting system. This research is a qualitative research with a descriptive approach. Data obtained through interviews and documentation from the agency.The result of this study indicate that the income accounting system applied at the Manado City Investment and One Stop Integrated Service Office is not adequate, this can be seen from the process of recording ITPMB retribution income which only record the Levies Determination Letter while accounting records in the preparation of financial statements are carried out by other agencies.Keywords: DPMPTSP, Accounting system, Income, Retribution ITPMB.